MEMICU VISUALISASI DAN KREATIVITAS DALAM PEMBELAJARAN MATEMATIKA MEMBENTUK KARAKTER POSITIF SISWA - Edy Surya (JURNAL TEMATIK, 2014)
Achievement various Indonesian student in International Olympic event apparently did not make the quality of Indonesian students increases. On the contrary , about 76.6 percent of junior high school students turned out to be judged